Software abstractions for mobile RFID‐enabled applications. (31st August 2011) - Carreton, Andoni Lombide; Pinte, Kevin; Meuter, Wolfgang De
SUMMARY: Our everyday environments may soon be pervaded with radio frequency identification (RFID) tags integrated in physical objects. These RFID tags can store a digital representation of the physical object and transmit it wirelessly to pervasive, context‐aware applications running on mobile devices. However, communicating with RFID tags is prone to many failures inherent to the technology. This hinders the development of such applications, as traditional programming models require the programmer to deal with the RFID hardware characteristics manually. On the other hand, traditional RFID middleware focuses on limited scenarios in an enterprise context and not on general ubiquitous computing scenarios. In this paper, we extend the ambient‐oriented programming paradigm to program RFID applications, by considering RFID tags as intermittently connected mutable proxy objects hosted on mobile distributed computing devices, and detail our prototype implementation. Copyright © 2011 John Wiley & Sons, Ltd.